Characterization of In Vitro-Generated and Clinical Optochin-Resistant Strains of Streptococcus pneumoniae Isolated from Argentina - Cortes, Paulo (2008)
Optochin susceptibility is a key test used for pneumococcal diagnosis, but optochin-resistant (Optr) pneumococci have been reported in the last 2 decades. In this work, we characterized eight Optr clinical strains which presented a new mutation, G47V, a predominant A49S mutation (recently reported in Brazil) and A49T. These mutations were found in the c subunit of the F0F1 ATPase encoded by the atpC gene, and W206C was found in the a subunit encoded by the atpA gene. The Optr clinical isolates were analyzed by BOX PCR, multilocus sequence typing, and serotype and antimicrobial resistance profiles, and they showed no epidemiological relationship. To characterize the Optr mutations that could emerge among clinical strains, we studied a pool of spontaneous Optr colonies obtained in vitro from the virulent D39 strain. We compared the atpAC mutations of these Optr pneumococci (with or without passage through C57BL/6 mice) with those described in the clinical isolates. This analysis revealed three new mutations, G47V and L26M in the c subunit and L184S in the a subunit. Most of the mutations identified in the laboratory-generated Optr strains were also found in clinical strains, with the exception of the L26M and L184S mutations, and we suppose that both mutations could emerge among invasive strains in the future. Considering that atpAC are essential genes, we propose that all spontaneous mutations that confer in vitro optochin resistance would not present severe physiological alterations in S. pneumoniae and may be carried by circulating pneumococcal strains.